2019
DOI: 10.1007/s10618-019-00651-1
|View full text |Cite|
|
Sign up to set email alerts
|

A unified view of density-based methods for semi-supervised clustering and classification

Abstract: Semi-supervised learning is drawing increasing attention in the era of big data, as the gap between the abundance of cheap, automatically collected unlabeled data and the scarcity of labeled data that are laborious and expensive to obtain is dramatically increasing. In this paper, we first introduce a unified view of density-based clustering algorithms. We then build upon this view and bridge the areas of semi-supervised clustering and classification under a common umbrella of density-based techniques. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…These are soft rather than hard constraints and used to guide the selection of clusters. Gertrudes et al [ 19 ] further extended this approach by an alternative HDBSCAN selection method that directly uses labels instead of turning them into pairwise constraints. We will explain this version in more detail in Section 3.2.2 , and also include it in our experiments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These are soft rather than hard constraints and used to guide the selection of clusters. Gertrudes et al [ 19 ] further extended this approach by an alternative HDBSCAN selection method that directly uses labels instead of turning them into pairwise constraints. We will explain this version in more detail in Section 3.2.2 , and also include it in our experiments.…”
Section: Related Workmentioning
confidence: 99%
“…Gertrudes et al [ 19 ] suggested to directly use labels instead of pairwise constraints. The authors argued that this prevents a bias towards should-not-link relations when adding new constraints, and also requires less effort.…”
Section: The Hdbscan Algorithmmentioning
confidence: 99%
“…HDBSCAN* has been generalized to perform not only constraint‐based semi‐supervised clustering (Campello et al, ), but also label‐based semi‐supervised clustering and classification (Gertrudes et al, , ). Novel combinations of building‐blocks from different algorithms such as HDBSCAN*, HISSCLU, and SSDBSCAN have also been successfully attempted (Gertrudes et al, , ).…”
Section: Semi‐supervised Density‐based Clusteringmentioning
confidence: 99%
“…The red boxes correspond to the optimal selection of clusters performed by algorithm FOSC, which is an optional postprocessing routine used by HDBSCAN*, with its default stability criterion. This figure was reproduced using the R package "dbscan," with the toy data set "moons," following the codes in the package vignettes HDBSCAN* has been generalized to perform not only constraint-based semi-supervised clustering (Campello et al, 2015), but also label-based semi-supervised clustering and classification (Gertrudes et al, 2018(Gertrudes et al, , 2019. Novel combinations of building-blocks from different algorithms such as HDBSCAN*, HISSCLU, and SSDBSCAN have also been successfully attempted (Gertrudes et al, 2018(Gertrudes et al, , 2019.…”
Section: Semi-supervised Density-based Clusteringmentioning
confidence: 99%
See 1 more Smart Citation